Innovative Disruption: The Case of the Diamond Industry - Rarick, Charles A.; Angriawan, Arifin (Journal of Strategic Innovation and Sustainability, 2017)
For many decades the diamond industry remained stable with De Beers firmly in control of supply and generating demand. The diamond cartel has since ended as outside suppliers of natural stones entered the market but the potential for the greatest change comes from outside the traditional industry and the technology brought to the marketplace. Diamonds no longer need to be mined but can now be produced in a high-tech manufacturing facility, creating not an artificial diamond, but one that is chemically identical to natural diamonds. This innovative disruption in the diamond industry has gained momentum and threatens the entire structure of the industry.